Mapping the Communication Patterns of Adolescents - West, Lloyd W. (Canadian Journal of Counselling and Psychotherapy, 2012)
The current academic interest in interpersonal communication is noted and a rationale and technique for mapping the self-disclosure patterns of adolescents is presented. An attempt is made to link the study of interpersonal communication to the mainstream of the ecological systems approach to the behavioral sciences. Counsellors are encouraged to experiment with the clinical usage of the SDIA and to report their experiences in the various publications of the field.